Polymorphisms in the promoter region of the bovine lactoferrin gene influence milk somatic cell score and milk production traits in Chinese Holstein cows. (December 2015) - Mao, Yongjiang; Zhu, Xiaorui; Xing, Shiyu; Zhang, Meirong; Zhang, Huimin; Wang, Xiaolong; Karrow, Niel; Yang, Liguo; Yang, Zhangping
Abstract: Lactoferrin is an iron-binding protein found in cow's milk that plays an important role in preventing mastitis caused by intramammary infection. In this study, 20 Chinese Holstein cows were selected randomly for PCR amplification and sequencing of the bovine lactoferrin gene promoter region and used for SNP discovery in the region between nucleotide positions − 461 to − 132. Three SNPs (− 270 T > C, − 190 G > A and − 156 A > G) were identified in bovine lactoferrin, then Chinese Holstein cows (n = 866) were genotyped using Sequenom MassARRAY (Sequenom Inc., San Diego, CA) based on the previous SNP information in this study, and the associations between SNPs or haplotype and milk somatic cell score (SCS) and production traits were analyzed by the least squares method in the GLM procedure of SAS. SNPs − 270 T > C and − 156 A > G showed close linkage disequilibrium (r 2  = 0.76). The SNP − 190 G > A showed a significant association with SCS, and individuals with genotype GG had higher SCS than genotypes AG and AA. Associations were found between the SNPs − 270 T > C and − 190 G > A with SCS and the milk composition. The software MatInspector revealed that these SNPs were located within several potential transcription factor binding sites, including NF-κB p50, KLF7 and SP1, and may alter gene expression, but further investigation will be required to elucidate the biological and practical relevance of these SNPs. Highlights: Three SNPs were identified in the BLF promotor region in Chinese Holstein. The SNP − 190 G > A showed significant effects on SCS. The SNPs − 270 T > C and − 190 G > A showed significant effects on milk composition.